2014
DOI: 10.1192/bjp.bp.113.131938
|View full text |Cite
|
Sign up to set email alerts
|

Rates of violence in patients classified as high risk by structured risk assessment instruments

Abstract: BackgroundRates of violence in persons identified as high risk by structured risk assessment instruments (SRAIs) are uncertain and frequently unreported by validation studies.AimsTo analyse the variation in rates of violence in individuals identified as high risk by SRAIs.MethodA systematic search of databases (1995-2011) was conducted for studies on nine widely used assessment tools. Where violence rates in high-risk groups were not published, these were requested from study authors. Rate information was extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 68 publications
0
58
0
6
Order By: Relevance
“…Current risk assessment instruments, however, have been limited by low-to-moderate accuracy, 6 poor reporting standards, 7 and inconsistent definitions of what constitutes high risk 8 . The tools have rarely been developed in individuals with psychosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Current risk assessment instruments, however, have been limited by low-to-moderate accuracy, 6 poor reporting standards, 7 and inconsistent definitions of what constitutes high risk 8 . The tools have rarely been developed in individuals with psychosis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of epidemiological, cohort, and case-control studies has shown associations between the risk factors described in this guideline and medium-to long-term relative risk of aggression in populations (Coid et al 2006;Doyle and Dolan 2006;Doyle et al 2012;Elbogen and Johnson 2009;Elbogen et al 2006;Eriksson et al 2011;Falk et al 2014;Harford et al 2013;Swanson et al 1990;Ten Have et al 2014;Van Dorn et al 2012;Whittington et al 2013;Witt et al 2013). However, there is no evidence that assessment of any of these factors can predict aggression in an individual (Buchanan et al 2012;Fazel et al 2012;Large et al 2011b;Rossegger et al 2013;Singh et al 2011Singh et al , 2014Thomas et al 2005). Similarly, no study has supported the ability of a specific rating scale to predict aggression in an individual.…”
Section: Guideline IV Assessment Of Risk For Aggressive Behaviorsmentioning
confidence: 94%
“…Although structured assessments of aggression risk have been developed and studied, none has sufficient predictive validity to identify individuals at high aggression risk in clinical settings (Buchanan et al 2012;Fazel et al 2012;Large et al 2011b;Rossegger et al 2013;Singh et al 2011Singh et al , 2014Thomas et al 2005). Accordingly, estimation of an individual patient's risk for aggression is ultimately a matter of clinician judgment that requires synthesizing the available information and deciding how to weigh the contributions of multiple factors, including those that may prevent the patient from acting on aggressive ideas.…”
mentioning
confidence: 99%
“…Over 10% -40% of mental health admissions are admitted to address aggression and violence issues [24,25]. Many patients arrive to medical and mental health facilities with existing aggression and violence issues as reasons for admission to mental health facilities.…”
Section: Patient Factors Admission Risk Assessment For Safetymentioning
confidence: 99%
“…Strong clinical admission assessment is one of the most vital interventions to prevent healthcare violence [25]. It is imperative that an efficient violence prevention plan include a risk assessment on admission as a critical part of a comprehensive mental health assessment.…”
Section: Patient Factors Admission Risk Assessment For Safetymentioning
confidence: 99%